2021
DOI: 10.3390/su13041787
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management. The Disconnection between Normative and SMEs Reality

Abstract: Waste generation is a critical factor in global environmental degradation, where SMEs have been historically relevant yet underestimated. This study covers the issue of the disconnection between the normative and SMEs reality. Therefore, this research aims to investigate the relationship between waste management norms and their application in Chilean SMEs. For context, Chile is the nation that generates the most amount of waste per capita in the region. Nevertheless, the country also has one of the most rigoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…Other studies have also revealed that the drivers Green Innovation include government policies [3,7,15,18]. Doran and Ryan [23] suggest regulatory or regulatory pressures can encourage SMEs intention to adopt Green Innovation.…”
Section: Adoption Of Green Innovation In the Context Of External Envi...mentioning
confidence: 99%
“…Other studies have also revealed that the drivers Green Innovation include government policies [3,7,15,18]. Doran and Ryan [23] suggest regulatory or regulatory pressures can encourage SMEs intention to adopt Green Innovation.…”
Section: Adoption Of Green Innovation In the Context Of External Envi...mentioning
confidence: 99%
“…The preceding is by the trade policies implemented in recent years by several countries to curtail the introduction of plastic waste (de Medio Ambiente y Recursos Naturales, 2021). Therefore, Latin American developing countries require systems that provide solutions to move, classify and process solid waste after its useful life (Villegas Pinuer et al, 2021).…”
Section: Importance Of Polymers Classificationmentioning
confidence: 99%
“…Pero, Villegas et al (2021) advierte que no existe una normatividad clara y precisa de disposición de RS para la actividad privada como es el caso de las PYME en la Región de Chile encontrándose hallazgos como: La ausencia de una norma de desperdicio flexible y adecuada para las PYMES que considere sus características y limitaciones prácticas, la dificultades con el manejo y disponibilidad de materias primas sostenibles, la necesidad de apoyo directo para PYMES, reflejadas en herramientas como subsidios, ayudas financieras y asistencia técnica para abordar su gestión de residuos. Por tanto, es necesario un sentido holístico para abordar de forma eficaz la situación de la gestión de residuos de las PYME.…”
Section: Conclusiones Y Objetivos De Los Artículos Revisadosunclassified
“…Villegas et al 2021) los gestores de las PYMES sí consideraron establecer diferentes iniciativas e incentivos para reducir la generación de residuos en sus actividades, en función de su interacción diaria con sus grupos de interés. En primer lugar, incentivos económicos a través de reducciones de impuestos y/o ayuda financiera para invertir en el proceso de producción más limpia.…”
unclassified